Helpful explanatory models for somatoform symptoms (HERMES): study protocol of a randomised mixed-methods pilot trial - Bernd Löwe; Angelika Weigel; Paul Hüsing; Tim C Olde Hartman; Lisbeth Frostholm (BMJ Open)
Introduction Persistent somatic symptoms (PSS) are common both in the general population and primary care. They are bothersome in terms of psychological and somatic symptom burden. Health professionals often struggle with communication, as there is a lack of scientifically supported explanatory models for PSS or a focus merely on somatic aspects of the complaints, which both frustrate patients’ needs. The objective of the present study is therefore to develop a psychoeducational intervention based on a current evidence-based explanatory model, to examine its feasibility and form the basis for a large-scale randomised controlled trial.Methods and analysis In a randomised controlled mixed-methods pilot trial, 75 adult psychosomatic outpatients with PSS (duration of symptoms ≥6 months) and accompanying psychological (Somatic Symptom B-Criteria Scale total score ≥18) and somatic symptom burden (Patient Health Questionnaire-15 score >10) and no prior psychosomatic treatment will be eligible. Participants will be presented with either the explanatory model without (intervention group 1, n=25) or with elements of personalisation (intervention group 2, n=25). Participants in the control group (n=25) will receive information on current PSS guidelines. Participants will be blinded to group assignment and interventions will be shown on tablet computers at the outpatient clinic. After 1 month, qualitative follow-up telephone interviews will be conducted. As primary outcomes, mean changes in psychological and somatic symptom burden will quantitatively be compared between groups, respectively. Behavioural change mechanisms and feasibility of the three interventions will be evaluated using quantitative and qualitative measures.Ethics and dissemination Ethics approval has been granted by the medical ethics board of the Hamburg Medical Chamber (PV5653). Results from this study will be published in peer-reviewed journals and presented at national and international conferences.Trial registration number DRKS00018803.